Systematic Evaluation of Skin and Adnexa in Mutant Laboratory Mice. Issue 3 (3rd September 2014) - Silva, Kathleen A.; Kennedy, Victoria E.; Sundberg, John P.
Abstract: The skin and its adnexa (hair and nails) comprise one of the easiest organ systems to evaluate, as they are the most accessible. However, mice are small and have lots of very fine hairs of multiple types. Thus, while major abnormalities are obvious, subtle abnormalities or the basis for these defects can be difficult to define. To assist in outlining basic approaches to evaluating mice clinically as well as microscopically with the help of a pathologist, methods are provided here that are used routinely in many laboratories. The mouse is a very useful mammalian model system for studying normal and abnormal (disease) development, and there is a high degree of correlation not only with human biology and medicine but with that of most other mammalian species. Utilizing basic approaches standardizes analysis and provides quality samples for analysis. Curr. Protoc. Mouse Biol . 4:105‐119 © 2014 by John Wiley & Sons, Inc.